Virulence Pattern of Pyricularia oryzae Pathotypes Towards Blast Monogenic Lines - Siti Norsuha Misman,; Mohd Shahril Firdaus Ab Razak,; Nur Syahirah Ahmad Sobri,; 3 Latiffah Zakaria, (Tropical Life Sciences Research, 2021)
Rice blast caused by Pyricularia oryzae (P. oryzae) is one of the most serious diseases infecting rice worldwide. In the present study, virulence pattern of six P. oryzae pathotypes (P0.0, P0.2, P1.0, P3.0, P7.0 and P9.0) identified from the blast pathogen collected in Peninsular Malaysia, were evaluated using a set of 22 IRRI-bred blast resistance lines (IRBL) as well as to determine the resistance genes involved. The information on the virulence of the blast pathotypes and the resistance genes involved is important for breeding of new rice variety for durable resistance against blast disease. The IRBL was established from 22 monogenic lines, harbouring 22 resistance genes [Pia, Pib, Pii, Pit, Pi3, Pi5(t), Pish, Pi1, Pik, Pik-s, Pik-m, Pik-h, Pik-p, Pi7(t), Pi9, Piz, Piz-5, Piz-t, Pi19, Pi20(t), Pita-2, and Pita=Pi4(t)]. Based on the disease severity patterns, the tested pathotypes were avirulence towards seven IRBLs [IRBLi-F5, IRBLk-Ka, IRBLkh-K3, IRBLz-Fu, IRBLsh-S, IRBLPi7 (t) and IRBL9-W] of which these IRBLs harbouring Pii, Pik, Pik-h, Piz, Pish, Pi7(t) and Pi9 resistance genes, respectively. Therefore, the results suggested that the seven IRBLs carrying seven resistance genes [Pii, Pik, Pik-h, Piz, Pish, Pi7(t) and Pi9] would be suitable candidates of resistance genes to be incorporated in new breeding lines to combat the current blast pathotypes in the field. Karah padi yang disebabkan oleh Pyricularia oryzae merupakan salah satu penyakit paling signifikan yang memberi kesan terhadap tanaman padi di seluruh dunia. Dalam kajian ini, corak kevirulenan enam patotip, P0.0, P0.2, P1.0, P3.0, P7.0 dan P9.0 yang dikenal pasti dari pencilan P. oryzae yang dikumpul dari Semenanjung Malaysia, dinilai menggunakan satu set 22 galur rintangan biakan karah-IRRI (IRBL) serta untuk menganggar gen rintangan yang terlibat. Maklumat mengenai kevirulenan patotaip karah dan gen rintangan terlibat adalah penting untuk pembiakbakaan varieti padi baru untuk kerintangan terhadap penyakit karah. IRBL dibangunkan dari 22 galur monogen, mengandungi 22 gen rintangan [Pia, Pib, Pii, Pit, Pi3, Pi5(t), Pish, Pi1, Pik, Pik-s, Pik-m, Pik-h, Pik-p, Pi7(t), Pi9, Piz, Piz-5, Piz-t, Pi19, Pi20(t), Pita-2, and Pita=Pi4(t)]. Berdasarkan corak tindakbalas penyakit, patotip yang diuji adalah avirulens terhadap tujuh IRBL [IRBLi-F5, IRBLk-Ka, IRBLkh-K3, IRBLz-Fu, IRBLsh-S, IRBLPi7(t) dan IRBL9-W] yang mengandungi gen rintangan Pii, Pik, Pik-h, Piz, Pish, Pi7(t) dan Pi9, masing-masing. Oleh itu, hasil kajian mencadangkan tujuh IRBL yang membawa tujuh gen rintangan [Pii, Pik, Pik-h, Piz, Pish, Pi7(t) dan Pi9] boleh menjadi calon gen rintangan yang sesuai untuk digabungkan ke dalam galur pembiakbakaan baharu untuk memerangi patotip karah di lapangan.